Citizenship education for VET students : learning through active participation - Höhns, Gabriela [Verfasser] (My University, 2020)
"Democratic education (DE) can be defined as learning about, for and/or through democracy. 'Learning through' should be the best way of DE for vocational learners who, compared to academic learners, are equally intelligent and more 'hands-on'. However, researchers such as Gordon (e.g., 2006) and Öhrn et al. (2011) argued that pupils' living democracy is hardly compatible with the social structuring of schooling. This paper, drawing, like Öhrn et al. on Bernstein's (e.g., 1990, 2000) code theory, exploits the theory's special potential to theoretically outline alternative modalities of education (cf. Moore 1984). Briefly, Bernstein's 'code' is a function of classifications (boundaries, resulting from power relations) and framings (control over the interaction). From Öhrn et al.'s findings, the paper highlights critical structural factors of schooling that encumber DE as 'learning through': interrelations between the programmes' prestige, the classification of learners and the classification in the curriculum organisation. The paper, then, argues that a change in the underlying macro-social power relations, from state and pedagogic field to agents from the community, leads to changes in the critical classifications, and concurrently eludes narrow technical training. The paper concludes that this theoretically constructed modality of education supports acquirers' legitimate control-taking over issues of pedagogic interaction (framing) and the possibility of DE as 'learning through' for vocational learners." (Authors' abstract, BIBB-Doku)
Keywords: T 2.1 Bildungstheorien; L 3.3 Lehrer-Lerner-Interaktion; Demokratie; Bildungstheorie; Bernstein, Basil; Unterrichtsgestaltung; Schüler; Partizipation; Lehrer-Schüler-Beziehung; Citizenship Education